O ruído em odontologia e seus reflexos na qualidade de vida - Schettini, Sonia Regina Lazarotto (2015)
Exposure to high levels of noise can cause irreversible hearing damage and physiological changes, triggering from psychological disorders to changes in biological rhythms. In a dental office there are devices that produce noise and according to their intensity and frequency may cause effects on the quality of life of professionals. Objective: To analyze the perception of the hearing health of dentists and relate it to the quality of life Method: This is a quantitative cross-sectional study using two questionnaires, one addressing issues of perception and hearing care knowledge and other Specific Quality of Life (SF 36) applied to dentists in the city of Curitiba, State of Parana. Results: participants were 54 dentists and 59.2% female and 40.7% male. Among men, 66.7% are over 40 years of age and 61.9% over 20 years of service. Among women 66.7% have from 20 to 40 years of age and time of service of up to 20 years (66.7%). Regarding the knowledge about the effects of noise, 73% know the effects of noise. The dentists report that the noise was little addressed in curricular matters graduation (20.3%) and only 25.7% received information on the harmful effects of noise; 59.2% are aware of ways to protect themselves from the noise, and the use of hearing protection was reported by 51.8% but 94.4% do not use hearing protection. As for the perception of noise in the workplace, 79.6% considers harmful noise, but does not verify 85.1% in the catalogs of manufacturers of equipment noise level; the high-speed handpiece was named the noisiest equipment in the office (92.5%). With reference to Quality of life was observed in the mean scores that the functional capacity domain had the best score (91.1) and the pain domain had the lowest average (22.2) followed by general health (41). Through the Student t test verified the existence of gender differences to the average of the following areas: pain (p = 0.0025), vitality (p = 0.0228) and mental health (p = 0.0009), being worse among men. Using the Spearman correlation coefficient, there was a correlation between the domains functional capacity, age (p = 0.0158) and time since graduation (p = 0.0111) among men. In women the correlation was found between the domains formed vitality and time (p = 0.0318). Noise levels found in this study had values between 56.1 dBA minimun and 77 dBA maximum in private practice and in public offices between 62.3 dBA minimun and 80 dBA maximum. These values are below the tolerance limits established in legislation, but are above the recommended value for acoustic comfort and may cause damage to health professionals. Conclusion: The noise is present in the workplace of dentists, but it is perceived lack of awareness by professionals of their effects on health and its effects on quality of life.